Morbidity in post-earthquake camps for temporary housing, armenia, colombia (2002)
A cross-sectional study was carried out in camps of temporary housing facilities after the earthquake occurred in the city of Armenia, January 25, 1999, in order to study the morbidity and identify possible differences between camps which were established, either spontaneously or induced, as an emergency post-disaster measure. 75 temporary camps were studied, 36 of them were induced and 39 were spontaneous. Data collection on morbidity was carried out by a survey besides obtaining information from community health care workers assigned to the camps. The most prevalent disease found was acute diarrheal disease, 32.4%, followed by acute respiratory infections, 24.1%. In spontaneous camps, compared with indiced camps, the risk of lice infection (OR: 1.6; 95% CI: 1.4-1.9), acute respiratory infections (OR: 1.2, 95% CI: 1.1-1.4), hepatitis (OR: 2.4; 95% CI: 1.5-3.9) and malaria (OR: 8.2 95% CI: 1.7-53) was greater. Organization of post-disaster camps must be a well-planned activity in order to decrease the morbidity in the affected populations.